GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG STUNTING DI DESA MUDAL MOJOTENGAH WONOSOBO - Indrawati Aris Tyarini; Ari Setyawati; Farihah Indriani; Dewi Candra Resmi; Siti Khoiriyah (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Pupose This study aims to describe the level of knowledge of mother about stunting in Mudal Village, Mojotengah District, Wonosobo Regency. Method this research is quantitative with descriptive method. Respondent in this study were mother who had toddlers in Mudal Village with a sampling technique using total sampling as many as 75 respondents. Data analysis using univariate test. Results the results of the study showed that the age of the respondents was in category of 26-35 years (73,4%). The most dominant source of information is electronic media (73,4%). The most dominant level of knowledge is at the medium level knowledge (64%). Conclusion the level of knowledge determined the occurrence of stunting in toddlers.